Egg Yolk and Glycerol Requirements for Freezing Boar Spermatozoa Treated with Methyl beta-Cyclodextrin or Cholesterol-loaded Cyclodextrin - Blanch, Eva; Tomás, Cristina; Hernandez, Marta; Roca, Jordi; Martinez, Emilio A.; Vazquez, Juan M.; Mocé, Eva (2017)
Egg yolk (BY) and glycerol are common constituents of extenders used for sperm cryopreservation. It has been demonstrated that using cholesterol-loaded cyclodextrins (CLC) improves sperm cryosurvival in several species. However, standard freezing extenders might not be the most appropriate for CLC-treated sperm. This study evaluated the EY and glycerol requirements for freezing. CLC-treated boar spermatozoa. Semen samples from 34 ejaculates coming from 4 boars were used. Each ejaculate was split into three aliquots: one was used untreated (control), and the other two were treated with 1 mg of CLC or methyl-beta-cyclodextrin/120 x 10(6) sperm for 15 min at 22 C prior to cryopreservation. Our results indicated that reducing the concentration of EY was detrimental for sperm viability after thawing (31.57 +/- 2 vs. 19.89% +/- 2 for 20 and 10% EY, respectively; P < 0.05), even in semen treated with CLC. On the other hand, it was observed that the traditional concentration of Glycerol (3%) was not the appropriate for freezing CLC-treated sperm (61.10 +/- 3 vs. 47.87% +/- 3 viable sperm for control and CLC-treated sperm, respectively; P <0.05). Thus, CLC-treated sperm showed a higher tolerance to high glycerol concentrations (5%) in terms of sperm viability (59.19% +/- 3) than non-treated sperm (45.58% +/- 3; P<0.05). Therefore, it could be necessary to modify the freeling extenders for CLC-treated sperm. Nevertheless, additional studies will be needed to evaluate alternative cryoprotectants and to determine the effect of high glycerol concentrations on sperm functionality.